Sepsis is a major determinant of outcome in HIV/AIDS critically ill patients - Japiassú, André M. (2010)
Fundação Oswaldo Cruz. Instituto de Pesquisa Clínica Evandro Chagas. Unidade de Terapia Intensiva. Rio de Janeiro, RJ, Brasil.